A matemática financeira e a inclusão bancária dos alunos do ensino médio - Pegoretti, Jordon Luiz (2015)
This paper deals with Financial Mathematics in high school and its importance to the household finances and the conscious credit, seeking to prepare students for banking inclusion. Therefore, we proposed activities that address the matter and how it is relevant to relationships with banks and / or financial. The methodology is based on an exploratory survey of employees of a bank city of Linhares-ES, responsible for customer service, credit analysis and sale of products and services to individual and corporate person. The research aims to verify the knowledge level of the population from the point of view of banking. With the results, have been proposed activities involving loans, using credit card and overdraft, focused on conscious credit and to find solutions to the growing household debt. The final considerations underline the importance of financial education quality and how it will influence the individual's choices for life. As contributions, research leaves us lessons and challenges. Lessons when we review the survey results with the bank and as the theme have been poorly addressed in schools, reflecting the Brazilian population, and challenges us to change the course of this history and begin a process of reduction of household debt through awareness of our students